Classification of In Vitro Phage–Host Population Growth Dynamics - Patricia E. Sørensen; Duncan Y. K. Ng; Luc Duchateau; Hanne Ingmer; An Garmyn; Patrick Butaye (Microorganisms, 2021)
The therapeutic use of bacteriophages (phage therapy) represents a promising alternative to antibiotics to control bacterial pathogens. However, the understanding of the phage–bacterium interactions and population dynamics seems essential for successful phage therapy implementation. Here, we investigated the effect of three factors: phage species (18 lytic E. coli-infecting phages); bacterial strain (10 APEC strains); and multiplicity of infection (MOI) (MOI 10, 1, and 0.1) on the bacterial growth dynamics. All factors had a significant effect, but the phage appeared to be the most important. The results showed seven distinct growth patterns. The first pattern corresponded to the normal bacterial growth pattern in the absence of a phage. The second pattern was complete bacterial killing. The remaining patterns were in-between, characterised by delayed growth and/or variable killing of the bacterial cells. In conclusion, this study demonstrates that the phage–host dynamics is an important factor in the capacity of a phage to eliminate bacteria. The classified patterns show that this is an essential factor to consider when developing a phage therapy. This methodology can be used to rapidly screen for novel phage candidates for phage therapy. Accordingly, the most promising candidates were phages found in Group 2, characterised by growth dynamics with high bacterial killing.